Abordagem sócio-espacial: rumo a assessoria problematizadora - Luiz Felipe Velloso Leal (2021)
This dissertation seeks to contribute to the construction of a socio-spatial theory based on the mobilization of some extension work influenced by Direct Technical Consultancy built by the Integration Office and linked to the Architecture and Urbanism course at PUC -MG. Social-spatial self-management is the notion adopted as reference to establish a horizon of radical transformation, in which the capitalist mode of production would be overcome. To this end, the concept of reproduction of the social relations of production developed by Lefebvre is treated in the light of this social-spatial perspective, in order to indicate characteristics of the movement of capital through and in the production of urban space. The autonomist praxis elucidated by Cornelius Castoriadis also composes this self-management horizon, taking into account the production of social relations constituted, in part, by subjectivities that present a split represented in the figure of the Self and the Other. The autonomy inscribed in the proposal of socio-spatial self-management is, therefore, characterized both by praxis at the level of local situations, directly involved in the consultancy work, and by global horizons of emancipation in relation to the dynamics of the current mode of social production. In this way, problematizing consultancy means establishing efforts towards this autonomy, based on practices that are less tied to the productivist character of mere problem solving and more committed to the construction of environments that can favor the emergence of new problems, and with them, new learning. Following this reasoning, problematization-learning was a term adopted to point out directions to be taken by educational situations that characterize contacts between technical and popular knowledge. Thus, the processes that derive from the encounter between technician and poor dweller, recurrent in urban architecture consultancy, are emphasized in opposition to the heteronomous spatial products, which appear as a non-negotiable need of the consulted. Therefore, the reported work experiences reveal how indispensable it would be to assume the pedagogical character of the socio-spatial approach, betting that non-heteronomous learning processes can be activated through critical problematizing engagements and exercises. Socio-spatial pedagogy, besides naming a study group of which this author is a member, would be a fundamental contribution to the construction of socio-spatial theory, which in the case of this research, serves as a guideline to discuss educational aspects present in consultancy practices.